Mycorrhizal Association of Terrestrial Orchids of Cycloops Nature Reserve, Jayapura - VERENA AGUSTINI; SUPENI SUFAATI; SUHARNO SUHARNO (Biodiversitas Journal of Biological Diversity, 2009)
Study on exploration of mycorrhizal association of terrestrial orchid of Cycloops Nature Reserve, Jayapura was done. Theaims of this study were to collect terrestrial orchid and to isolate orchid mycorrhiza associated with it. Survey method was used in this study. Isolation of orchid mycorrhiza was based on modified methods of Masuhara and Katsuya (1989). The result showed that there were 10 species of terrestrial orchid in this area. Eleven orchid mycorrhizal fungi were isolated from five terrestrial orchids. Among them, 6 isolates were associated with Geodorum sp. From the seventeen mycorrhizal fungi, 3 isolates were identified, namely Rhizoctonia sp., Tulasnella sp., and Ceratorhiza sp, while the last fourteen isolates have not been identified yet. Mostly, each isolate has a specific orchid host, except species G (sp. G) which associated with Phaius sp. and Plocoglottis sp.Key words: terrestrial orchid, orchid mycorrhiza, Mt. Cycloops Nature Reserve, Jayapura